Onboard Charging DC/DC Converter of Electric Vehicle Based on Synchronous Rectification and Characteristic Analysis - Haijun Tao; Guopeng Zhang; Zheng Zheng (Journal of Advanced Transportation)
The DC/DC converter is the core part of the two-stage electric vehicle Onboard Charger. At present, the phase-shifted full-bridge soft-switching DC/DC converter has problems such as difficulty in commutation of the lagging leg, voltage fluctuation on the secondary side of the transformer, and low efficiency. A full-bridge DC/DC converter with two clamp diodes and synchronous rectification is proposed in this paper. Clamping diodes are used to suppress the voltage oscillation of the secondary side of the transformer and provide the commutating energy of the lagging leg. Synchronous rectification reduces the loss of the switching device. The operating principle and control method of the DC/DC converter are analyzed, and the switching device loss is calculated. The simulation and experimental results show that, compared with the traditional DC/DC converter, the voltage impulse of the secondary side of the transformer is smaller, the efficiency is higher, and the soft switch can be realized in a wide load range, which satisfies the requirement of fast charging of vehicle-mounted batteries.